2014
DOI: 10.1039/c4ja00125g
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium isotope ratio measurements in environmental matrices by MC-ICP-MS

Abstract: Various stages of an analytical method for high-precision cadmium (Cd) isotope ratio measurements by MC-ICP-MS (sample preparation, matrix separation, instrumental analysis and data evaluation) were critically evaluated and optimized for the processing of carbon-rich environmental samples. Overall reproducibility of the method was assessed by replicate preparation and Cd isotope ratio measurements in various environmental matrices (soil, sediment, Fe-Mn nodules, sludge, kidney, liver, leaves) and was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
90
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(120 citation statements)
references
References 43 publications
(117 reference statements)
17
90
3
1
Order By: Relevance
“…6 20 suggested that incomplete oxidation of carbon might interfere during ion-exchange separation and suggested to remove organic-rich matrices through ashing.…”
Section: Chromatographic Separation Efficiency Influenced By Organic mentioning
confidence: 99%
See 4 more Smart Citations
“…6 20 suggested that incomplete oxidation of carbon might interfere during ion-exchange separation and suggested to remove organic-rich matrices through ashing.…”
Section: Chromatographic Separation Efficiency Influenced By Organic mentioning
confidence: 99%
“…Metallic elements and residual resin-derived organic compounds lead to inaccurate Cd isotope results. 32 Pallavicicini et al 20 suggest ashing of organic-rich matrices. Wei et al 5,6 removed the organic matter of plants by HClO4.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations